2020
DOI: 10.1001/jamanetworkopen.2019.20780
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Risk Factors With β-Amyloid Peptide and Tau Burdens in Cognitively Unimpaired Individuals and Its Interaction With Vascular Medication Use

Abstract: IMPORTANCE Vascular risk factors are associated with increased risk of Alzheimer disease (AD), but it is unclear whether there is a direct association of these risk factors with AD pathogenesis. OBJECTIVES To assess the associations of vascular risk factors with AD pathogenesis in asymptomatic individuals, and to test whether this association is moderated among individuals who use vascular medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
(98 reference statements)
1
36
0
Order By: Relevance
“…Additionally, Bowman and colleagues investigated the relationship between the BBB and the pathology of AD and found that dyslipidemia was prevalent in 47% of study participants with mild-to-moderate AD and 75% of those who had AD with BBB impairment, suggesting that dyslipidemia may play a role in decreasing BBB integrity [ 269 ]. Total cholesterol and low-density lipoprotein cholesterol levels have also been associated with increased Aβ burden in humans [ 224, 270 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…Additionally, Bowman and colleagues investigated the relationship between the BBB and the pathology of AD and found that dyslipidemia was prevalent in 47% of study participants with mild-to-moderate AD and 75% of those who had AD with BBB impairment, suggesting that dyslipidemia may play a role in decreasing BBB integrity [ 269 ]. Total cholesterol and low-density lipoprotein cholesterol levels have also been associated with increased Aβ burden in humans [ 224, 270 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…Retinal arteriolar central re ex to vessel width ratio in digital retinal photographs was signi cantly higher in APOE ε4 allele carriers (46), hence the retina may allow for noninvasive monitoring of the effects of APOE ε4 on the cerebrovascular disease. Similarly, as targeting vascular risk factors is being considered in AD prevention trials (50), retinal vascular assessments could offer a window for assessing the response to various interventions.…”
Section: Introductionmentioning
confidence: 99%
“…When examining the separate components of the risk score, it was found that body mass index, treatment with antihypertensive medication, systolic blood pressure and smoking status all significantly contributed to this effect [ 99 ]. Another study including controls with a positive family history for sporadic AD found no effect of vascular risk factors on entorhinal tau burden [ 58 ]. A large study in 434 controls did not find an association between white mater hyperintensities on MRI and increased [ 18 F]flortaucipir retention [ 36 ].…”
Section: Resultsmentioning
confidence: 99%